Przestrzeń w służbie funkcjonalności i rozwoju czytelnictwa, zamiast biblioteki w służbie przestrzeni = Space Serving Functionality and the Development of Reading, Rather than a Library Serving Space - Marchewska, Kamilla (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article outlines the conditions for wise and purposeful modernization, focusing more on functionality and the needs of readers rather than strictly aesthetic goals. It addresses questions on how to strategically plan and implement modernization efforts. The role of the local community and municipal authorities is also defined. The text discusses realistic planning, the importance of securing social conditions, and examines how to leverage the strengths of a project while managing its weaknesses. A key section of the article explores how to use the potential of library modernization to promote reading.
Keywords: modernizacja; infrastruktura; strategia; zarządzanie; rozwój; rozbudowa; planowanie; przestrzeń; projektowanie; celowość; estetyka; funkcjonalność; modernization; infrastructure; strategy; management; development; expansion; planning; space; design; purposefulness; aestetics; functionality